2020
DOI: 10.1007/s10584-020-02795-2
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing production and flow of freshwater ecosystem services in a managed Himalayan river system under uncertain future climate

Abstract: Future climate change will likely impact the multiple freshwater ecosystem services (fES) provided by catchments through their landscapes and river systems. However, there is high spatio-temporal uncertainty on those impacts linked to climate change uncertainty and the natural and anthropogenic interdependencies of water management systems. This study identifies current and future spatial patterns of fES production in a highly managed water resource system in northern India to inform the design and assessment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 72 publications
1
17
0
Order By: Relevance
“…Shrestha et al [71] investigated the widespread climate change impact on the Himalayan ecosystem and concluded that rate of warming is higher than the global average and will make the Himalayas more vulnerable to climate change. Several other studies also have similar findings on the impact of climate change on horticulture and water resources ecosystem in the Himalayas [72,73].…”
Section: Discussionsupporting
confidence: 65%
“…Shrestha et al [71] investigated the widespread climate change impact on the Himalayan ecosystem and concluded that rate of warming is higher than the global average and will make the Himalayas more vulnerable to climate change. Several other studies also have similar findings on the impact of climate change on horticulture and water resources ecosystem in the Himalayas [72,73].…”
Section: Discussionsupporting
confidence: 65%
“…Bhakra-Beas Management Board, State Water Resources and Irrigation Departments and hydropower companies). Historic meteorological data were available for the mountainous and hilly regions (Bannister et al 2019) and the plains (ERA-Interim downscaled with RegCM4 from CORDEX), while future projections of temperature and precipitation were sourced from the Climate Model Intercomparison Project Phase 5 (CMIP5) through the KNMI Climate Explorer (Trouet and van Oldenborgh 2013) and downscaled using the monthly delta change method (Momblanch et al 2020).…”
Section: Datamentioning
confidence: 99%
“…The Water Evaluation and Planning (WEAP) (Yates et al 2005) systems model was used to simulate multisectoral water allocations in the interlinked Beas-Sutlej river basins. The development, calibration and validation of the Beas-Sutlej WEAP model is fully detailed in Momblanch et al (2019aMomblanch et al ( , 2020, but is briefly described here. WEAP represents the main hydrological processes including snow and glacier accumulation and melt which are particularly relevant for Himalayan hydrology, water demands (i.e.…”
Section: Water Resource Systems Modelmentioning
confidence: 99%
“…The model of the Sutlej-Beas system used in this study has been developed at Cranfield University as part of SusHi-Wat (https://www.egis.hw.ac.uk/sushiwat), an international collaborative research on the Indian Himalayas, and has been published elsewhere (Momblanch et al 2020). The mountain hydrology is represented using the Rainfall-Runoff Soil Moisture Method (SMM) in WEAP in a semi-lumped fashion, considering 23 subcatchments and 600 m elevation bands which result in 165 spatial elements (i.e.…”
Section: Weap Modelmentioning
confidence: 99%